Distribution and length of osteophytes in the lumbar vertebrae and risk of rupture of abdominal aortic aneurysms: A study of dry bones from Chiang Mai, Thailand - Patcharin Chanapa (2018)
© 2014. Anatomy & Cell Biology. Vertebral osteophytes are a characteristic feature of intervertebral disc degeneration. In the lumbar spinal region, the two major structures in close proximity anterior to the spine are the inferior vena cava and the abdominal aorta, both of which have been reported to be affected by osteophytes. The purpose of this study was to determine the distribution, classification and lengths of osteophytes in the lumbar vertebrae. One hundred and eighty lumbar columns of 90 males and 90 females from Chiang Mai, Thailand, in the age range 15 to 96 years (mean age, 63 years) were collected. The measuring length of osteophytes was assessed on vertebral body and articular facet. Statistical analysis was performed by descriptive analysis, chi-square and Pearson Correlation. Lumbar osteophytes were presented in 175 specimens (97.2%), 88 males and 87 females. The highest frequency was at L4, most were on the superior, inferior surface of body and articular facet (39.7%, 38.4%, and 22%), respectively. The greatest mean length was 3.47±2.21 mm at L5, and the longest length of anterior superior surface of body was 28.56 mm. The osteophyte length was significantly correlated directly with age (P<0.01), and males were significantly greater than females (P<0.05). The highest prevalence of osteophytes was on the anterior side of superior surface of body (30.4%), and the classification was traction. It can be proposed that the abdominal aorta could be damaged, especially a risk of rupture of abdominal aortic aneurysm.